Effect of Cryopreserved Placenta Extract on LPO Intensity and Lipid Hydroperoxide Content in Rat Tissue in Norm and After General Acute Cooling - Prokopyuk, O. S.; Cheremskoy, A. K.; Nikitchenko, Yu. V.; Chizhevsky, V. V. (Problems of Cryobiology and Cryomedicine, 2005)
Effect of cryopreserved placenta extract on lipid peroxidation (LPO) intensity and lipid hydroperoxide content in Wistar line ratsâ€™ blood serum and liver, heart homogenates under normal conditions and following general acute cooling was studied. General acute cooling of animals was found to increase the LPO intensity as well as lipid hydroperoxide content in rat liver, heart tissues and blood serum. Introduction of cryopreserved placenta extract prevents LPO activation in all studied tissues of experimental animals and we believe this testifies to the activation of biochemical adaptation mechanisms, compensating cold-caused disorders. Â 